1989
DOI: 10.1063/1.456961
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation kinetics of aluminum cluster ions: Determination of cluster dissociation energies

Abstract: The photodissociation of aluminum clusters, Al+n (n=7–17), has been studied over a broad energy range (1.88–6.99 eV). Measurements of the lifetimes of the photoexcited clusters are described. Dissociation energies have been determined by comparing the measured lifetimes with the predictions of a simple RRKM model. The dissociation energies show an overall increase with cluster size, but there are substantial oscillations around n=7–8 and n=13–15. Cluster cohesive energies are derived from these results and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 40 publications
6
70
0
1
Order By: Relevance
“…We provide here a brief summary of the bibliography which is most relevant to the present work ͑for example, we do not mention many papers dealing with aluminum clusters with 2-12 atoms͒. Jarrold et al 11 performed collision-induced dissociation experiments on Al n + ͑n =3-26͒ and obtained enhanced cluster stabilities for Al 13 , Al 13 + , Al 14 + , and Al 23 + . Taylor et al 12 measured ultraviolet photoelectron spectra of Al n − with n =3-32 and found evidences of electron shell closings for sizes n = 13, 19, and 23.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We provide here a brief summary of the bibliography which is most relevant to the present work ͑for example, we do not mention many papers dealing with aluminum clusters with 2-12 atoms͒. Jarrold et al 11 performed collision-induced dissociation experiments on Al n + ͑n =3-26͒ and obtained enhanced cluster stabilities for Al 13 , Al 13 + , Al 14 + , and Al 23 + . Taylor et al 12 measured ultraviolet photoelectron spectra of Al n − with n =3-32 and found evidences of electron shell closings for sizes n = 13, 19, and 23.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al 12 measured ultraviolet photoelectron spectra of Al n − with n =3-32 and found evidences of electron shell closings for sizes n = 13, 19, and 23. Both Ray et al 13 and King and Ross 14 concluded that Al 15 + has a very low stability and/or dissociation energy. Saito et al 15 reported mass spectra of bare Al n + cluster ions and identified enhanced abundances for n = 14, 17, 20, 23, and 28.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations